2018
DOI: 10.3389/fpsyg.2018.00647
|View full text |Cite
|
Sign up to set email alerts
|

Reading Derived Words by Italian Children With and Without Dyslexia: The Effect of Root Length

Abstract: Children with dyslexia are extremely slow at reading long words but they are faster with stimuli composed of roots and derivational suffixes (e.g., CASSIERE, ‘cashier’) than stimuli not decomposable in morphemes (e.g., CAMMELLO, ‘camel’). The present study assessed whether root length modulates children’s morphological processing. For typically developing readers, root activation was expected to be higher for longer than shorter roots because longer roots are more informative access units than shorter ones. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
1
7
0
2
Order By: Relevance
“…Our results show that words with high suffix salience (i.e., longer suffixes and shorter stems) requires more fixation time than words with low suffix salience (i.e., shorter suffixes and longer stems). So, the paper by Burani et al , () and ours are showing two relevant aspects of complex word processing. The first one is that by increasing the perceptual salience of suffixes readers become more sensitive to them and the second one is that the longer the stem – and the shorter the suffix‐ the faster the processing in the first stages.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our results show that words with high suffix salience (i.e., longer suffixes and shorter stems) requires more fixation time than words with low suffix salience (i.e., shorter suffixes and longer stems). So, the paper by Burani et al , () and ours are showing two relevant aspects of complex word processing. The first one is that by increasing the perceptual salience of suffixes readers become more sensitive to them and the second one is that the longer the stem – and the shorter the suffix‐ the faster the processing in the first stages.…”
Section: Discussionsupporting
confidence: 52%
“…Our assumption goes in the same direction although it points further because it is that by increasing the perceptual salience of suffixes readers become more sensitive to them and therefore compositional route is favored in comparison to the direct route – or in terms of Burani, Marcolini Traficante and Zoccollotti (), the longer the morphemic constituent is, the more informative this reading unit (see also Kuperman et al , , for similar discussion about the interplay between suffix length and word frequency). An interesting issue to highlight from the paper by Burani et al , () is that they found similar results to ours, despite focusing on stem length. Indeed they found a facilitative effect by which words with longer stems required less time to be read than words with shorter ones.…”
Section: Discussionmentioning
confidence: 58%
“…The key finding of the present study is that while the presence of stems and suffixes did not provide an overall boost in letter detection in our visual one-back paradigm, the specific knowledge about stems and suffixes during childhood might slightly modulate letter coding strategies through the deployment of visual attention across letter strings (also see: Burani, Marcolini, Traficante, & Zoccolotti, 2018;Law et al, 2018). This modulation might be partly attributed to the frequency with which these orthographic units are encountered in written language.…”
Section: Discussionmentioning
confidence: 49%
“…The visual attention span hypothesis assumes that the ability to process multiple letters that make up a word is impaired in children with dyslexia and that this is due to a reduced visual attention span [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Whether this impairment is due to a reduced attention span or any other visual deficit depends on what is understood by ”attention span“.…”
Section: What Are Causes Of Dyslexia?mentioning
confidence: 99%